1977
DOI: 10.1111/j.2151-6952.1977.tb01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Learning at the Ohio Historical Center

Abstract: Educating museum visitors is nearly universally accepted as a central responsibility of museum people. The museum can be likened to a permanent storage battery of intellectual stimulation, a primary source of wonder and delight. A museum's atmosphere is casual, the pace and order are not forced. The visitor is free t o linger and backtrack. Museums have a tactile, kinetic, three-dimensional quality, involving more than one sense. It is rewarding to become involved with the exhibits through touching and feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Nevertheless, this study found little evidence of higher order thinking about the aquarium exhibit and program content, beyond the simple recall of facts.. These results are consistent with previous studies that have concluded that adult learning in science museum settings is characteristically low on Bloom's order of taxonomy (Adelman, Falk, and James 2000;Boggs 1977;Wellington 1990). 7 M5: Well, I guess I learned at the tropical zone they have these huge catfish and I didn't know that they eat fruits and berries, so I guess I learned that.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, this study found little evidence of higher order thinking about the aquarium exhibit and program content, beyond the simple recall of facts.. These results are consistent with previous studies that have concluded that adult learning in science museum settings is characteristically low on Bloom's order of taxonomy (Adelman, Falk, and James 2000;Boggs 1977;Wellington 1990). 7 M5: Well, I guess I learned at the tropical zone they have these huge catfish and I didn't know that they eat fruits and berries, so I guess I learned that.…”
Section: Resultssupporting
confidence: 89%
“…This type of learning is characterized by a strong sense of appreciation and recognition of marine life diversity and exceptionality, by the acknowledgment of the unique experience of being close to nature, and by the development of an emotional link with marine animals, particularly mammals. These outcomes support the notion that informal environments are settings that effectively foster affective responses among visitors (Boggs 1977;Falk and Dierking 2000;Wellington 1990).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…A significant difference in mean knowledge gain scores were found between the control (Brown, 1979;Peart, 1982;Stronck, 1983) and with that of other researchers (Boggs, 1977;Griggs, 1981;Screven, 1976;Shettel, 1973). These results also concur with other research in that although some knowledge was gained, it was precious little gain.…”
Section: Knowledge Gainsupporting
confidence: 47%
“…21 "Os museus proporcionam o seu mais frutífero serviço público justamente ao oferecer uma experiência educacional no seu mais amplo sentido: promovendo a habilidade de viver produtivamente numa sociedade pluralista e de contribuir com as resoluções dos desafios com os quais deparamos como cidadãos globais" (AAM, 1992: 6). 22 Flexer e Borun, 1984. 23 Boggs, 1977. Os pesquisadores constataram que a visita e a palestra produziam o mesmo grau de aprendizagem de conceitos de física, mas que a visita ao museu foi mais interessante e divertida para os estudantes. O ganho de uma visita ao museu, portanto, não está fundamentado na eficácia da transmissão de conteúdos, mas sim na relação entre prazer, entusiasmo e aprendizagem da ciência -os chamados ganhos afetivos (BORUN, op.cit;SCREVEN, 1991 (ALT, 1980;CONE & KENDALL, 1978;DIXON et al, 1974;GIGUÈRE, 1985 apud ALLARD e BOUCHER, op.cit.).…”
Section: Museus E Públicos: Breve Histórico De Mudançasunclassified